(untitled) (Scientific journal of the Fergana State University, 2025)
This article explores the main challenges in the art of public speaking, such as intense anxiety, fear, and losing composure during speech delivery, as well as alternative solutions to these issues. Studies show that approximately 77% of people suffer from glossophobia, or the fear of public speaking. This means nearly three-quarters of the world’s population are directly or indirectly affected by this problem. The causes of public speaking anxiety can range from a lack of self-confidence and fear of failure to insufficient preparation before delivering a speech. Psychological research indicates that this issue stems not only from individual traits but also from societal influences and upbringing. Public speaking is a skill that can be mastered with time and practice. This article highlights effective strategies to manage anxiety, such as deep breathing techniques, mindfulness exercises, and thorough preparation. Additionally, it emphasizes the importance of attending workshops and training programs dedicated to public speaking.